The Valley of the Kings : a site management handbook - Weeks, Kent R. (American University in Cairo Press, 2014)
This volume, the result of 25 years of work by the Theban Mapping Project at the American University in Cairo, traces the history of the Valley of the Kings and offers specific proposals to manage the site and protect its fragile contents. At the same time, it recognizes the need to provide a positive experience for the thousands of visitors who flock here daily. This is the first major management plan developed for any Egyptian archaeological site, and as its proposals are implemented, they offer a replicable model for archaeologists, conservators, and site managers throughout Egypt & the region